The Influence Of Executive’s Characteristics And Financial Distress On Tax Avoidance With Litigation Risk As A Moderating Variable - Dien Shahani, Kamila; Subandi, Hendi (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to examine the influence of executive’s characteristics and financial distress on tax avoidance, with litigation risk as a moderating variable. Using a purposive sampling technique, 25 energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 were selected as samples. The data were analyzed using panel data regression with the Common Effect Model (CEM) in EViews 12 Student Lite. The results show that executive’s characteristics significantly affect tax avoidance and that litigation risk weakens the influence of executive’s characteristics on tax avoidance. Meanwhile, financial distress has no significant effect on tax avoidance, and litigation risk does not moderate the relationship between financial distress and tax avoidance.